Artificial Propagation of Gattan (Barbus xanthopterus Heckel) in Basrah- Iraq - Al Mukhtar, Mustafa A.; Jaber, Jasim H. Amer A.; Alzaidi, Faleh M.; Hassan, Auda M.; Hussoni, Khalid H.; Ghani, Sajad A.; Al Shawei, Nasir H. (Iraqi Journal of Aquaculture, 2022)
Gattan (Barbus xanthopterus Heckel) was artificially propagated in marine science center fish hatchery- University of Basrah, During Spring 2009. The brooders were collected from Al-Huwaizah Marsh (which were bring in to the hatchery directly) and Al-Therthar reservoir (which were reared in earthen ponds). The efforts to collect brooders from Al- Kut dam were failed, because of water shortage. The brooders ranged between 1500-6500 gr in weight and II-V year age. The gonads of Al- Huwaizah marsh brooders were in good maturity stage, The GSI was ranged between 3.66-11.03%, and in ripe maturity stage, while the brooder's gonads of Al-Therthar reservoir were in developing stage, with GSI ranged between 1.1-1.3 %, and this result was agreed with the previous studies. "Aquacalm" substance was used for sedation; it was found that the best concentration for the sedation of Gattan was 1 ppm. The best treatment for the induced spawning of Gattan was the Carp pituitary gland extract (CPG), with a dosage of 6 mg/ kg, in two injections, each with 3 mg/kg, with 12 h interval. Two fishes from Al- Therthar reservoir were responding to this treatment, with weight of 1750 and 1500g. 350 g of good quality eggs was obtained from the first fish. All the males give small quantity of milt the milt was added to the eggs without water for mixing. Then the eggs were covered with water for. Fertilization rate was 88%. The fertilized eggs washed with water only, from brooders rearing tank for 20min. Then incubated in Zoug jars with a rate off 70 g / jar, incubation temperature ranged between 22- 24°C. The hatching completed after 72 h, with 80 % hatching rate. The larvae start feeding after three days; it reached weight of 5.3 ± 0.80 during the first ten days. The larvae were reared in floating cages. The daily growth was 1.94 mg during the 21 days of rearing. During this period it reached a weight of 48 mg and 23 mm in length.